Chromosomal instability-induced senescence potentiates cell non-autonomous tumourigenic effects - He, Qianqian (2018)
Chromosomal instability (CIN), a high rate of chromosome loss or gain, is often associated with poor prognosis and drug resistance in cancers. Aneuploid, including near-polyploid, cells contain an abnormal number of chromosomes and exhibit CIN. The post-mitotic cell fates following generation of different degrees of chromosome mis-segregation and aneuploidy are unclear. Here we used aneuploidy inducers, nocodazole and reversine, to create different levels of aneuploidy. A higher extent of aneuploid and near-polyploid cells in a given population led to senescence. This was in contrast to cells with relatively lower levels of abnormal ploidy that continued to proliferate. Our findings revealed that senescence was accompanied by DNA damage and robust p53 activation. These senescent cells acquired the senescence-associated secretory phenotype (SASP). Depletion of p53 reduced the number of senescent cells with concomitant increase in cells undergoing DNA replication. Characterisation of these SASP factors demonstrated that they conferred paracrine pro-tumourigenic effects such as invasion, migration and angiogenesis both in vitro and in vivo. Finally, a correlation between increased aneuploidy and senescence was observed at the invasive front in breast carcinomas. Our findings demonstrate functional non-equivalence of discernable aneuploidies on tumourigenesis and suggest a cell non-autonomous mechanism by which aneuploidy-induced senescent cells and SASP can affect the tumour microenvironment to promote tumour progression.